2018
DOI: 10.1155/2018/1805354
|View full text |Cite
|
Sign up to set email alerts
|

Nitroso‐Oxidative Stress, Acute Phase Response, and Cytogenetic Damage in Wistar Rats Treated with Adrenaline

Abstract: This study is aimed at analysing biochemical and genetic endpoints of toxic effects after administration of adrenaline. For this purpose, the study was carried out on Wistar rats and three doses of adrenaline were used: 0.75 mg/kg, 1.5 mg/kg, and 3 mg/kg body weight. To achieve these aims, we investigated the effects of adrenaline on catalase (CAT), Cu, Zn-superoxide dismutase (SOD), malondialdehyde (MDA), nitrite (NO2−), carbonyl groups (PCC), and nitrotyrosine (3-NT). Total activity of lactate dehydrogenase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 70 publications
0
13
0
2
Order By: Relevance
“…Bellomo et al [13] reported that activation of type α1 adrenaline receptors could cause excessive renal vasoconstriction and decreased renal blood flow in models of healthy renal hemodynamics. Radaković et al [14] described that adrenaline induction increased ROS and caused a disruption in oxidant/antioxidant balance. Considering these results and the developmental mechanism of EIAKI (i.e., ROS and renal ischemia), we suspect that the vasopressors may have affected the onset or worsening of EIAKI by increasing ROS, exacerbating vasoconstriction, and forming a vicious cycle of diminished renal hemodynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Bellomo et al [13] reported that activation of type α1 adrenaline receptors could cause excessive renal vasoconstriction and decreased renal blood flow in models of healthy renal hemodynamics. Radaković et al [14] described that adrenaline induction increased ROS and caused a disruption in oxidant/antioxidant balance. Considering these results and the developmental mechanism of EIAKI (i.e., ROS and renal ischemia), we suspect that the vasopressors may have affected the onset or worsening of EIAKI by increasing ROS, exacerbating vasoconstriction, and forming a vicious cycle of diminished renal hemodynamics.…”
Section: Discussionmentioning
confidence: 99%
“…During stress condition, a high amount of catecholamines is released to prepare the body for "fight or flight" response (Ranabir and Reetu, 2011). Radaković et al (2018) showed that adrenaline caused an increase in total activity of LDH, LDH1 and LDH2 isoenzymes in rats. Drouet et al (2015) showed significant increases (1.9 fold-increases) in plasma levels of LDH in rats after a model of acute restraint stress in relation to control group.…”
Section: Discussionmentioning
confidence: 99%
“…Adrenaline was found to induce MI by causing lipid peroxidation leading to depletion of cellular antioxidants ( Andreadou et al., 2009 ). In cardiomyocytes, adrenaline was shown to increase lipid, protein, and DNA damage with overproduction of nitrosative derivatives ( Radaković et al., 2018 ). Since ROS play a crucial role in the pathogenesis of MI, efforts have been directed towards the use of natural products possessing anti-oxidant activity as adjuvants with few side effects and great safety in treatment of MI ( Li et al., 2012 ).…”
Section: Introductionmentioning
confidence: 99%